Exploring Multimodality in English-Language Music Video: A Study of Sade’s Audiovisual Work - Shykina, Nataliia (Studia Philologica, 2024)
In contemporary linguistic research, the study of multimodality has gained prominence due to technological developments that have introduced novel tools for conveying information within a unified communicative space. Music videos, which combine verbal, auditory, and visual elements, exemplify polysemiotic unity, rendering them an optimal subject for investigating the interactions between modes in multimodal discourse. The objective of this study is to identify the characteristics of the integration of modes for meaning-making in the music video of the British band Sade for the song “No Ordinary Love.” In particular, the aim is to ascertain how the conceptual metaphors present in the song’s lyrics influence the imagery in the video. By employing tools from cognitive linguistics and semiotics, the study conducted a detailed analysis of how verbal, auditory, and visual modes interact to uncover the dominant conceptual metaphors and their role in shaping meaning. The study identified several conceptual metaphors, including LOVE AS A RESOURCE, LOVE AS A STRUGGLE, and LOVE AS A TRANSIENT EXPERIENCE. The study of the audial mode revealed a clear correlation between the melancholic mood of the composition and the conceptual metaphors identified. The visual mode was studied with a focus on the analysis of the lyrical heroine’s appearance and gestures in the music video. In particular, the visual representation of the latter was examined in order to ascertain how it explicates conceptual metaphors. The synergy of these three modes – verbal, audial and visual – resulted in the formation of a complex image of the Little Mermaid from the tale by H. Ch. Andersen in the music video.